Risk Identification of Online Learning - Riyan Maulana; Emil Biyansyahna; Siti Afriani (el-Nizami : Jurnal Manajemen Pendidikan, 2024)
Riyan Maulana 1*, Emil Biyansyahna 2, Siti Afriani (3) 1 Alwashliyah University Banda Aceh 2 Syiah Kuala University 3 STIK Pante Kulu Banda Aceh *Corresponding author: riyanmaulana@unadabna.ac.id Abstract The COVID-19 pandemic has forced the education sector to shift to online learning due to social distancing, utilizing information and communication technology for teaching and learning. However, this transition presents risks such as inequality of technology access, decreased student engagement, and psychosocial impacts. This study aims to identify the risks of online learning through systematic literature review (SLR) to support effective risk management and inform education policy in the digital era. The research used the SLR method, with searches on scientific databases such as Google Scholar, Scopus, and ScienceDirect. Inclusion criteria included English and Indonesian journals (2017-2022), using the keywords "online learning risk" and "online education risk management". The selection process followed the PRISMA protocol, resulting in 34 relevant journals after rigorous screening. The analysis showed that one journal addressed online education policy, highlighting the risks of regulatory unpreparedness and internet access in remote areas. Sixteen journals focused on higher education, identifying risks such as low student motivation, digital plagiarism and lack of lecturer technology training. Seventeen journals addressed primary and secondary schools, emphasizing the risks of unequal access to devices, mental health disorders, and decreased social interaction. Key risks include technical, pedagogical and psychosocial aspects. Integrated risk management, such as improved digital infrastructure, technology training and mental health support, is needed for mitigation. This research recommends further empirical studies in the Indonesian context to support sustainable online learning. The findings enrich the educational literature with a comprehensive risk management framework.